A beautiful mind [videorecording (DVD)] - Howard, Ron, 1954-; Crowe, Russell, 1964-; Harris, Ed, 1950-; Connelly, Jennifer; Nasar, Sylvia (Universal Studios Canada, 2002)
Dramatic biography of John Nash, a mathematical genius, who made an astonishing discovery early in his career and stood on the brink of international acclaim. But the handsome and arrogant Nash soon found himself on a painful and harrowing journey of self-discovery. After many years of struggle, he eventually triumphed over his schizophrenia, and finally, late in life, received the Nobel Prize.